Absorption of Tar Content in Producer Gas using Used Cooking Oil in a Packed-bed Column - Firman Asto Putro; Joko Waluyo; Bahaul Fahmi Al Haq; Wahyu Nur Hidayat; Sunu Herwi Pranolo (Program studi Teknik Kimia UNS, 2023)
Abstract. The tar content in producer gas may cause crusting on the engine if it is utilized as a fuel gas, thus it needs to be removed. This study aims to determine the liquid phase mass transfer coefficient in process of removing tar from producer gas in a packed-bed contactor column. This process is carried out continuously using used-cooking oil as absorbent. This was carried out by contacting the producer gas as a product of cacao pod-husk gasification at temperature range of 491-940°C at a certain counter-current flow rate with used-cooking oil in a column with a Raschig ring packing bed. The study used packed-bed materials with specific surface areas of 29.3927 m²/m³, 49.7532 m²/m³, 95.4113 m²/m³, 96.8182 m²/m³, 101.6840 m²/m³, and 105.0128 m²/m³, and with the linear velocity of used-cooking oil ranging from 0.0229 m/s to 0.0827 m/s. A mass transfer coefficient mathematical model has been constructed based on the research results. The model applies to the ranges (As.dt), (DL/dt.vL), and (µL / ρL.vL.dt) from 2.2397 to 8.0020, 2.26.10-10 to 1.72.10-9, and 0.0331 to 0.3102, respectively, with an average error of 9.33%. The average tar removed was 87%.Keywords:Producer gas, mass transfer coefficient, packed-bed column, tar, used-cooking oil